CULTURAL, PHYSIOLOGICAL AND MOLECULAR CHARACTERIZATION OF ACTINOMYCETES FROM THE SOIL OF MUZAFFARPUR DISTRICT - KHWAJA SALAHUDDIN; UTKARSHINI; SANJU KUMARI; SANTOSH KUMAR (The Bioscan, 2011)
Actinomycetes constitute a formidable group of industrially important microorganisms that have been greatly explored for the production of secondary metabolites. The solid samples were collected from litchi garden, rhizoplane of herbaceous plants and water logged land. A total of 72 strains were isolated on seven culture media and cultural characteristics of these strains were observed. The viable count was found to be maximum (12.82x 104 ) per gram dry weight of litchi garden soil on Czapek-Dox agar medium. Least population was recorded on water logged soil. Moderate to heavy sporulation was noticed in some of the strains. White and gray pigments remained dominant on all media used. The utilization of different carbon sources by these strains was reported. On the basis of pigment production, sporulation and luxuriant growth, eight strains out of 72 could be singled out, subcultured and purified in the laboratory conditions. Antagonistic effects especially against six antibiotics were noticed and some of the strains exhibited resistance to ampicillin, kanamycin and streptomycin. The evidence for the presence of plasmid was searched out on agarose gel electrophoresis and later electrophoretic separation of sharp bands on agarose gel was also observed.